2020
DOI: 10.18203/2320-1770.ijrcog20204784
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal outcome in severe preeclampsia and eclampsia at the Rivers State university teaching hospital, Nigeria

Abstract: Background: Severe preeclampsia and eclampsia remain a challenge in tropical obstetric practice. It is a major contributor to feto-maternal morbidity and mortality in developing countries. This study seeks to determine the prevalence, associated risk factors and the feto-maternal outcome of severe preeclampsia and eclampsia at the rivers state university teaching hospital (RSUTH).Method: A retrospective study of all women who had severe preeclampsia and eclampsia and were delivered at the RSUTH in a two-year p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…This issue usually necessitates a surgical delivery to prevent birth complications including shoulder dystocia, which is difficult to cure. Cesarean sections lessen dangers but increase issues [21]. Cesarean sections may cause newborn respiratory difficulties, longer hospital stays, and higher healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
“…This issue usually necessitates a surgical delivery to prevent birth complications including shoulder dystocia, which is difficult to cure. Cesarean sections lessen dangers but increase issues [21]. Cesarean sections may cause newborn respiratory difficulties, longer hospital stays, and higher healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, two separate studies conducted in 2 different states in Southern Nigeria showed a prevalence of 0.44% and 1.66% for Enugu and Lagos in year 2011 and 2008 respectively [17] [18], while a study conducted in a state in Northern Nigeria in 2011 showed that eclampsia had a maternal fatality of 42% [19]. Furthermore, a 2020 study conducted by Awoyesuku et al [10] in River State showed that eclampsia had a prevalence of 2.85% among 4496 deliveries reported over the 2 years' duration of the study.…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors that are associated with eclampsia are similar to those of preeclampsia or gestational hypertension [1]. Several studies globally [8] [9] [10] have identified these factors to include: • Black and Hispanic race • Young age, • Nulliparity, • Multifetal gestation, • Multiparous pregnant women with a new partner, • Unbooked cases,…”
Section: Introductionmentioning
confidence: 99%